2020
DOI: 10.18203/2349-3291.ijcp20202624
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, epidemiological and laboratory characteristics of children with febrile seizures

Abstract: Background: Febrile seizure is the most common type of seizure disorder that occurs in children aged 6-60 months. Recurrences are common. This study was conducted to evaluate the epidemiology, clinical profile and laboratory parameters of children presenting with febrile seizure in a teaching hospital.Methods: This was a descriptive retrospective study among children presenting with febrile seizure admitted to KIMS, Bengaluru from March (2018-2019). Children between six months to five years were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
5
1
1
Order By: Relevance
“…Our study found that FS peaked during second year of life which corroborates to the finding from India and China. 18 , 19 However Deng et al from Malaysia found its peak in the first year of life. 20 In this study, FS predominantly occurred in male children similar to other studies from Nepal and abroad.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that FS peaked during second year of life which corroborates to the finding from India and China. 18 , 19 However Deng et al from Malaysia found its peak in the first year of life. 20 In this study, FS predominantly occurred in male children similar to other studies from Nepal and abroad.…”
Section: Discussionmentioning
confidence: 99%
“…14 Shankar P et al also report a family history in around 30% children. 17 The difference in the incidences may be due to genetic predisposition in various populations. It can largely be affected by the lack of awareness about past seizures in the parents or any members of the family.…”
Section: Discussionmentioning
confidence: 99%
“…Criteria for the inclusion of retrieved publications to accomplish our specified aims were: (1) investigation of at least 100 CFS cases, (2) determination of the time of day of each CFS by report of a parent/caretaker or the arrival time to the health care facility according to the patient's medical record, (3) presentation in tabular or graphic form of the number or proportion of children experiencing a FS per 1, 4, or 6‐hour time interval of the 24 h, and (4) documentation of febrile state by measurement of body temperature at home within 24 h of the onset of the CFS and/or upon arrival to the emergency department (ED), clinic, or hospital. One 13 of the 11 retrieved publications summarized the findings of a previous publication 16 ; one 19 presented no time‐of‐day data; and one 20 was deficient both in the number of cases ( N = 60) and clock‐time definition of “afternoon,” “evening,” “morning,” and “night” for which data were presented, leaving the time series data of eight qualifying articles that utilized diverse methods (see accompanying Supporting Information for a thorough description of the methods of each investigation) representing the time‐of‐day manifestation of 2461 CFSs.…”
Section: Methodsmentioning
confidence: 99%
“…Medline, Google Scholar, and Cochrane databases were searched for publications in any language using the terms of "childhood febrile seizure" paired with "timeof-day," "24 hour," "diurnal," and "circadian." Eleven potentially relevant articles [13][14][15][16][17][18][19][20][21][22][23] were retrieved, with six of them also addressing monthly or seasonal variation in CFSs. [13][14][15][16][17][18] Therefore, the same databases were further explored using the terms "childhood febrile seizure" paired with "seasonal," "annual," and "circannual"; however, it yielded no additional articles that reported time-of-day data.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation